2015
DOI: 10.1007/s00253-015-6766-z
|View full text |Cite
|
Sign up to set email alerts
|

Whey-derived valuable products obtained by microbial fermentation

Abstract: Whey, the main by-product of the cheese industry, is considered as an important pollutant due to its high chemical and biological oxygen demand. Whey, often considered as waste, has high nutritional value and can be used to obtain value-added products, although some of them need expensive enzymatic synthesis. An economical alternative to transform whey into valuable products is through bacterial or yeast fermentations and by accumulation during algae growth. Fermentative processes can be applied either to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 105 publications
1
53
0
4
Order By: Relevance
“…Studies have assessed the recovery of whey as a source of lactic acid, xanthan gum, lactitol and lactulose. In this respect, it is interesting to consider the production of bioplastics and derivatives thereof from whey (Mollea et al, 2013;Pescuma et al, 2015). Global production of whey is estimated at around 90 9 10 6 ton per year and growing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have assessed the recovery of whey as a source of lactic acid, xanthan gum, lactitol and lactulose. In this respect, it is interesting to consider the production of bioplastics and derivatives thereof from whey (Mollea et al, 2013;Pescuma et al, 2015). Global production of whey is estimated at around 90 9 10 6 ton per year and growing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional artisanal methods of making various cheese have been replaced by industrial production processes along with decline of Kazak nomadic customs. The microorganisms contribute to cheese flavor through their lysis and the release of intracellular enzymes which mainly determine the development of flavor during the cheese ripening (Fasoli et al, 2015;Padilla, Belloch, López-Díez, Flores, & Manzanares, 2014;Pescuma, de Valdez, & Mozzi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is likely that different animal host genetic profiles, lifestyles and habitats, and diets may lead to differences in milk composition. Previous studies have demonstrated that the chemical characteristics of cervid milk are different from that of other domestic dairy species1213. Reindeer milk has the highest nutritional content (carbohydrate, fat, proteins, branch chain fatty acids, and immune factors) among non-bovine mammals2.…”
mentioning
confidence: 99%